Social representations of History at the service of teaching practice in Higher Education - Íñigo Mugueta Moreno (Universidad de La Rioja, 2016)
This study sets out to analyse some of the most widespread representations of History maintained by Primary Education Degree students, and to set up an efficient teaching procedure to develop critical capacity among these students so that they can approach historical knowledge, nowadays so subject to clichés spread by the social networks, the Internet and a whole and varied "transmedia universe". Social representations of History among the students will be analysed through questionnaires, based on qualitative and quantitative criteria, while the teaching methods, developed together with students from the Teacher Training Degree course, the Master's Degree Course for Secondary Teacher Training, and the Pedagogical Training Course for Primary Education Degree students (always university students) will be assessed qualitatively as a unit. The results will enable us to analyse some of the advantages and difficulties involved in an active teaching methodology based on the interests and previous knowledge of the students, even when these constitute alternative realities to scientific knowledge.